Solid-state battery positive electrode material, multi-layer structure precursor and preparation and application of solid-state battery positive electrode material and multi-layer structure precursor
By using a multi-layer structure precursor design and M-element doping to cover the shell in the positive electrode material of solid-state battery, the problems of insufficient structural stability of the positive electrode material and interface side reaction in the prior art are solved, and better cycling and electrochemical performance are achieved.
Patent Information
- Application Number
- CN202510090704.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-29
AI Technical Summary
The structural stability of the existing solid-state battery positive electrode materials is insufficient, resulting in poor circulation performance, and side reactions are prone to occur at the interface between the positive electrode materials and the electrolyte, affecting the electrochemical performance.
The multi-layer structure precursor design is adopted, the loose layer and the dense layer are arranged intertwined, and the shell is doped with M element to coat it, improve the lithium ion embedding and disengagement channels, and suppress the side reaction between the positive electrode material and the electrolyte interface.
It improves the structural stability of the positive electrode material and the circulation performance of solid-state batteries, enhances the interface conductivity, suppresses side reactions, and improves electrochemical performance.
Smart Images

Figure CN119898830A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of battery technology and relates to a multilayer structure precursor of a solid-state battery positive electrode material, and in particular to a solid-state battery positive electrode material, a multilayer structure precursor, and preparation and application thereof. Background Art
[0002] Solid-state batteries have the significant advantages of high energy density and high safety, becoming the next generation of high-performance lithium batteries. From the perspective of performance comparison, in theory, solid-state batteries are superior to liquid batteries in various indicators such as ion conductivity, energy density, high voltage resistance, high temperature resistance and cycle life. They take into account the high energy density and high safety characteristics that traditional liquid lithium batteries cannot take into account, making them ideal batteries for electric vehicles.
[0003] However, the problem faced by the development of solid-state battery positive electrode materials in the prior art is that during the process of lithium removal or lithium insertion of the positive electrode active material, its unit cell parameters will inevitably shrink or expand, causing the volume deformation of the positive electrode active material particles. At the same time, since the solid electrolyte and the electrode particles are in rigid contact, it is easy to cause the contact between the electrode particles and between the electrode particles and the electrolyte to deteriorate during the cycle, or the stress accumulation causes the mechanical properties of the electrolyte to fail, which in turn leads to the attenuation of the battery's electrochemical performance. Secondly, the interface where the positive electrode material contacts the solid electrolyte will react to form a complex interface film, which increases the charge transfer impedance and thus affects the electrochemical performance of the solid-state battery.
[0004] CN112607791A discloses a multilayer lithium ion battery precursor, the precursor comprising: xMn(OH) 2-y Ni(OH) 2-z Co(OH)2, wherein x+y+z=1, 0.1≤x≤0.5, 0.3≤y≤0.8, 0≤z≤0.2; the precursor is a spherical particle with a multilayer structure, the innermost layer of which is Mn x Ni y-b Co z-c (OH) 2-2b-2c , the middle layer is bNi(OH)2, and the outermost layer is cCo(OH)2, where 0≤b≤y, 0≤c≤z.
[0005] CN117735629A discloses a precursor for a positive electrode material of a lithium ion battery. The core of the precursor is a hydroxide of nickel, cobalt and manganese, and the outer part of the core is a multilayer structure formed by alternating hydroxides of lanthanum, aluminum, iron, chromium, magnesium and zinc and hydroxides of nickel, cobalt and manganese, and the innermost layer and the outermost layer of the multilayer structure are both hydroxides of lanthanum, aluminum, iron, chromium, magnesium and zinc. In addition, the invention discloses a coprecipitation preparation process of the above-mentioned precursor. The hydroxide of lanthanum, aluminum, iron, chromium, magnesium and zinc is coated on the surface of the hydroxide of nickel, cobalt and manganese, and is used as a repeating component unit to form a precursor. After the precursor of this structure is mixed with lithium and sintered, the hydroxide of lanthanum, aluminum, iron, chromium, magnesium and zinc is converted into a high entropy oxide, which can accelerate the transmission of lithium ions, and the interval setting of the high entropy oxide can effectively inhibit the cracking of secondary particles, hinder the side reaction between the electrode and the electrolyte, and promote the positive electrode-electrolyte interface dynamics, thereby improving the electrochemical performance.
[0006] The precursors of solid-state battery positive electrode materials disclosed in the prior art all have certain defects. The prepared solid-state battery positive electrode materials have insufficient structural stability, which leads to poor cycle performance of solid-state batteries, and side reactions occur at the interface between the solid-state battery positive electrode materials and the electrolyte, which leads to poor electrochemical performance of solid-state batteries. Therefore, it is very important to develop and design a new type of solid-state battery positive electrode material, multilayer structure precursor, and its preparation and application. Summary of the invention
[0007] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a solid-state battery positive electrode material, a multilayer structure precursor and its preparation and application. The multilayer structure precursor of the solid-state battery positive electrode material provided by the present invention is designed with a multilayer structure, and the loose layer and the dense layer are interlaced in the multilayer structure design. On the one hand, it can effectively release the accumulated stress generated during the de-lithiation or lithium insertion process of the positive electrode material, reduce the volume deformation of the positive electrode material particles, thereby improving the structural stability of the material and the cycle performance of the solid-state battery; on the other hand, the multilayer structure can improve the lithium ion embedding and extraction channels, thereby improving the electrochemical performance of the solid-state battery; in addition, the outermost layer of the multilayer structure is designed to be an M element doped coating shell. The introduction of the M element doped coating shell can improve the conductivity of the interface layer, inhibit the side reaction between the positive electrode material and the solid electrolyte interface, and thus make the positive electrode material and the solid-state battery have good electrochemical performance.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a multilayer structure precursor of a solid-state battery positive electrode material, wherein the multilayer structure precursor comprises a seed crystal, an intermediate coating layer, and an M element doped coating shell;
[0010] The intermediate coating layer includes at least one stacked structure, and the stacked structure includes a first coating layer and a second coating layer with different porosities that are stacked.
[0011] The multilayer structure precursor of the solid-state battery positive electrode material provided by the present invention is designed with a multilayer structure, and the loose layers and the dense layers are arranged in an interlaced manner. On the one hand, it can effectively release the accumulated stress generated during the de-lithiation or lithium insertion process of the positive electrode material, reduce the volume deformation of the positive electrode material particles, thereby improving the structural stability of the material and the cycle performance of the solid-state battery; on the other hand, the multilayer structure can improve the lithium ion embedding and extraction channels, thereby improving the electrochemical performance of the solid-state battery; in addition, the outermost layer of the multilayer structure is designed to be an M element doped coating shell. The introduction of the M element doped coating shell can improve the conductivity of the interface layer, inhibit the side reaction between the positive electrode material and the solid electrolyte interface, and thus make the positive electrode material and the solid-state battery have good electrochemical performance.
[0012] Preferably, the multi-layer structure precursor further comprises a secondary inner layer disposed between the seed crystal and the intermediate coating layer.
[0013] Preferably, the porosity of the seed crystal is 10-45%, for example, it can be 10%, 15%, 20%, 25%, 30%, 35%, 40% or 45%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0014] Preferably, the porosity of the sub-inner layer is 5-25%, for example, it can be 5%, 7%, 10%, 12%, 15%, 17%, 20%, 22% or 25%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0015] Preferably, in the stacked structure, the porosity of the first coating layer is greater than the porosity of the second coating layer.
[0016] Preferably, the porosity of the first coating layer in the stacked structure is independently 10-25%, for example, it can be 10%, 12%, 15%, 17%, 20%, 22% or 25%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0017] Preferably, the porosity of the second coating layer in the stacked structure is independently 1 to 20%, for example, it can be 1%, 3%, 5%, 7%, 10%, 12%, 15%, 17% or 20%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] Preferably, the porosity of the M element doped coating shell is 10-20%, for example, it can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0019] Preferably, the D50 particle size of the seed crystal is 0.5-2 μm, for example, 0.5 μm, 0.7 μm, 1 μm, 1.2 μm, 1.5 μm, 1.7 μm or 2 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0020] Preferably, the thickness of the secondary inner layer is 0.1-2.5 μm, for example, it can be 0.1 μm, 0.3 μm, 0.5 μm, 0.7 μm, 1 μm, 1.3 μm, 1.5 μm, 1.7 μm, 2 μm, 2.2 μm or 2.5 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0021] Preferably, the thickness of the first coating layer in the stacked structure is independently 0.5 to 2 μm, for example, it can be 0.1 μm, 0.3 μm, 0.5 μm, 0.7 μm, 1 μm, 1.3 μm, 1.5 μm, 1.7 μm or 2 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0022] Preferably, the thickness of the second coating layer in the stacked structure is independently 0.5 to 2 μm, for example, it can be 0.1 μm, 0.3 μm, 0.5 μm, 0.7 μm, 1 μm, 1.3 μm, 1.5 μm, 1.7 μm or 2 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0023] Preferably, the M element includes any one of Al, Nb, B, W or Zr or a combination of at least two thereof. Typical but non-limiting combinations include a combination of Al and Nb, a combination of Nb and B, a combination of W and Zr, or a combination of Al, Nb and B.
[0024] Preferably, the thickness of the M element doped coating shell is 0.01-1 μm, for example, 0.01 μm, 0.05 μm, 0.1 μm, 0.3 μm, 0.5 μm, 0.7 μm or 1 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] Preferably, the chemical formula of the multilayer structure precursor is Ni a Co b Mnc M d (OH)2; wherein, M is any one or a combination of at least two elements selected from Al, Nb, B, W, or Zr, 0.9 < a < 1, 0 < b ≤ 0.09, 0 < c ≤ 0.09, 0 < d < 0.05, and a + b + c + d = 1.
[0026] In the present invention, M is any one or a combination of at least two elements selected from Al, Nb, B, W, or Zr. Typical but non-limiting combinations include the combination of Al and Nb, the combination of Nb and B, the combination of W and Zr, or the combination of Al, Nb, and B.
[0027] In the present invention, 0.9 < a < 1. The value of a can be, for example, 0.91, 0.92, 0.94, 0.96, 0.98, or 1, but is not limited to the listed values. Other unlisted values within this range are equally applicable.
[0028] In the present invention, 0 < b ≤ 0.09. The value of b can be, for example, 0.01, 0.02, 0.03, 0.05, 0.07, or 0.09, but is not limited to the listed values. Other unlisted values within this range are equally applicable.
[0029] In the present invention, 0 < c ≤ 0.09. The value of c can be, for example, 0.01, 0.02, 0.03, 0.05, 0.07, or 0.09, but is not limited to the listed values. Other unlisted values within this range are equally applicable.
[0030] In the present invention, 0 < d < 0.05. The value of d can be, for example, 0.01, 0.02, 0.03, 0.04, or 0.05, but is not limited to the listed values. Other unlisted values within this range are equally applicable.
[0031] Preferably, the radius of the multi-layer structure precursor is 4 - 10 μm, which can be, for example, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, or 10 μm, but is not limited to the listed values. Other unlisted values within this range are equally applicable.
[0032] Preferably, the D50 particle size of the multi-layer structure precursor is 8 - 20 μm, which can be, for example, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, or 20 μm, but is not limited to the listed values. Other unlisted values within this range are equally applicable.
[0033] Preferably, the tapped density TD of the multi-layer structure precursor is 1.4 - 2.2 g / cm 3 , for example, it can be 1.4 g / cm 3 、1.5 g / cm3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.75g / cm 3 , 1.8g / cm 3 , 1.85g / cm 3 , 1.9g / cm 3 , 1.95g / cm 3 , 2g / cm 3 , 2.05g / cm 3 , 2.1g / cm 3 , 2.15g / cm 3 or 2.2g / cm 3 , but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] Preferably, the specific surface area of the multilayer structure precursor is 4 to 20 g / cm 3 , for example, it can be 4g / cm 3 , 6g / cm 3 , 8g / cm 3 、10g / cm 3 , 12g / cm 3 , 14g / cm 3 , 16g / cm 3 , 18g / cm 3 or 20g / cm 3 , but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] Preferably, the ratio of the (101) peak diffraction intensity to the (001) peak diffraction intensity of the multilayer structure precursor is 0.8 to 1.3, and the half-peak width of the (101) peak is 0.25 to 0.4.
[0036] The ratio of the (101) peak diffraction intensity to the (001) peak diffraction intensity of the multilayer structure precursor described in the present invention is 0.8 to 1.3, for example, it can be 0.8, 0.9, 1, 1.1, 1.2 or 1.3, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] The half-peak width of the (101) peak of the multilayer structure precursor in the present invention is 0.25 to 0.4, for example, it can be 0.25, 0.27, 0.3, 0.32, 0.35, 0.37 or 0.4, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] In a second aspect, the present invention provides a method for preparing the multilayer structure precursor according to the first aspect, the preparation method comprising:
[0039] (1) adding a ternary metal solution, an alkali solution and a complexing agent solution to a reaction bottom solution in parallel, adjusting the pH, ammonia concentration, temperature and rotation speed of the reaction process, and performing a first stage of co-precipitation. When the precipitate reaches an initial target particle size, the reaction is stopped, and a first solid-liquid separation is performed to obtain seed crystals and a remaining reaction bottom solution;
[0040] (2) mixing the obtained seed crystals with water and adding the mixture into the remaining reaction base solution obtained in step (1) to obtain a slurry, and then adding the ternary metal solution, alkali solution and complexing agent solution to the obtained slurry in parallel to obtain a reaction slurry;
[0041] (3) adjusting the pH, ammonia concentration, temperature and solid content of the reaction slurry obtained in the previous step, and simultaneously adjusting the rotation speed, performing a coprecipitation reaction in a protective atmosphere, and stopping the reaction after obtaining a reaction solution containing the first target precipitate;
[0042] (4) adjusting the pH, ammonia concentration, temperature and solid content of the reaction solution obtained in step (3), and simultaneously adjusting the rotation speed, performing a coprecipitation reaction in a protective atmosphere, and stopping the reaction after obtaining a reaction solution containing the second target precipitate;
[0043] (5) If only one layer of the stacked structure is prepared, then directly start preparing the M element doped coating shell; if more than one layer of the stacked structure is prepared, then repeat step (3) and step (4) at least once, and then prepare the M element doped coating shell to obtain a multilayer structure precursor;
[0044] The method for preparing the M element doped coating shell is as follows: keeping the pH, ammonia concentration, temperature and solid content of the reaction solution obtained in the last step (4) unchanged, keeping the rotation speed unchanged, adding the M salt solution, the ternary metal solution, the alkali solution and the complexing agent solution to the reaction solution obtained in the last step (4) in parallel, carrying out a coprecipitation reaction in a protective atmosphere, and stopping the reaction after reaching the end target particle size to obtain the M element doped coating shell.
[0045] In the preparation method of the multilayer structure precursor provided by the present invention, the pH and ammonia concentration during the coprecipitation reaction will affect the looseness and density of each layer in the obtained multilayer structure precursor; when the pH value is higher and the ammonia concentration is larger, the particles in the layer formed during the coprecipitation reaction are more densely packed, and a dense layer with smaller porosity is formed; when the pH value is lower and the ammonia concentration is smaller, the particles in the layer formed during the coprecipitation reaction are more densely packed, and a loose layer with larger porosity is formed.
[0046] In the method for preparing the multilayer structure precursor provided by the present invention, the temperature will also affect the looseness and density of each layer in the obtained multilayer structure precursor, that is, it will affect the porosity of each layer, but the effect of temperature on porosity is smaller than that of pH and ammonia concentration.
[0047] In the preparation method of the multilayer structure precursor provided by the present invention, the porosity of different layers of the multilayer structure precursor is controlled by controlling the pH, ammonia concentration and temperature during the reaction process.
[0048] Preferably, the step between step (2) and step (3) further includes the preparation of a secondary inner layer, and the method for preparing the secondary inner layer is:
[0049] The pH, ammonia concentration, temperature and solid content of the reaction slurry obtained in step (2) are adjusted, and the rotation speed is adjusted simultaneously to carry out a coprecipitation reaction in a protective atmosphere to obtain a reaction slurry containing a precipitate of an intermediate target particle size.
[0050] Preferably, the molar concentration of metal ions in the ternary metal solution in step (1) is 0.1 to 5 mol / L, for example, 0.1 mol / L, 0.5 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L or 5 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0051] Preferably, the ternary metal solution in step (1) comprises nickel salt, cobalt salt and manganese salt, and the nickel salt, cobalt salt and manganese salt respectively and independently comprise any one or a combination of at least two of sulfate, nitrate, chloride and acetate. Typical but non-limiting combinations include a combination of sulfate and nitrate, a combination of nitrate and chloride, a combination of chloride and acetate, or a combination of sulfate, nitrate and chloride.
[0052] Preferably, the solvent in the ternary metal solution in step (1) comprises water.
[0053] Preferably, the pH of the reaction base solution in step (1) is 7.5-12, the ammonia concentration is 0.1-10 g / L, the temperature is 40-70° C., and the dissolved oxygen content is 1-3000 ppm.
[0054] The pH of the reaction base solution in step (1) of the present invention is 7.5 to 12, for example, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5 or 12, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0055] The ammonia concentration of the reaction base solution in step (1) of the present invention is 0.1 to 10 g / L, for example, 0.1 g / L, 0.5 g / L, 1 g / L, 2 g / L, 3 g / L, 4 g / L, 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L or 10 g / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0056] The temperature of the reaction base liquid in step (1) of the present invention is 40-70°C, for example, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C or 70°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0057] The dissolved oxygen content of the reaction base liquid in step (1) of the present invention is 1 to 3000 ppm, for example, 1 ppm, 5 ppm, 10 ppm, 20 ppm, 50 ppm, 100 ppm, 200 ppm, 300 ppm, 400 ppm, 600 ppm, 1000 ppm, 1500 ppm, 2000 ppm, 2500 ppm or 3000 ppm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0058] In the preparation method provided by the present invention, the amount of dissolved oxygen in the reaction bottom liquid will affect the size of the crystal nucleus. The higher the dissolved oxygen amount, the looser the core structure and the greater the core porosity. However, the dissolved oxygen amount should be within an appropriate range. If the porosity is too high, the core will be hollow during subsequent sintering into the positive electrode, affecting the positive electrode performance. In the preparation method described in the present invention, the amount of dissolved oxygen in the reaction bottom liquid is controlled to ensure that the multilayer structure precursor has a suitable porosity.
[0059] Preferably, in step (1), the pH of the reaction process is adjusted to 10-12, the ammonia concentration is 5-8 g / L, the temperature is 40-70° C. and the rotation speed is 350-500 rpm.
[0060] The pH of the reaction process in step (1) of the present invention is adjusted to 10-12, for example, it can be 0.1 g / L, 0.5 g / L, 1 g / L, 2 g / L, 3 g / L, 4 g / L, 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L or 10 g / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0061] The ammonia concentration for adjusting the reaction process in step (1) of the present invention is 5 to 8 g / L, for example, 5 g / L, 5.5 g / L, 6 g / L, 6.5 g / L, 7 g / L, 7.5 g / L or 8 g / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0062] Preferably, in step (1), sodium hydroxide solution and aqueous ammonia are used to adjust the pH and ammonia concentration of the obtained mixed solution.
[0063] The temperature of the reaction process in step (1) of the present invention is adjusted to 40-70°C, for example, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C or 70°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0064] The rotation speed of the reaction process in step (1) of the present invention is adjusted to 350-500 rpm, for example, 350 rpm, 380 rpm, 400 rpm, 420 rpm, 440 rpm, 460 rpm, 480 rpm or 500 rpm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0065] In the preparation method of the multilayer structure precursor provided by the present invention, the rotation speed during the coprecipitation reaction will also affect the looseness and density of each layer in the obtained multilayer structure precursor, that is, it will affect the porosity of each layer, but the effect of the rotation speed on the porosity is smaller than that of pH and ammonia concentration.
[0066] Preferably, the initial target particle size in step (1) is a D50 particle size of 0.5 to 2 μm, for example, 0.5 μm, 0.7 μm, 0.9 μm, 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm or 2 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0067] Preferably, the protective atmosphere in step (1) comprises nitrogen and / or an inert gas.
[0068] Preferably, the solid-liquid separation in step (1) further comprises washing and drying the obtained solid in sequence.
[0069] Preferably, in the method for preparing the secondary inner layer, the pH of the reaction slurry obtained in step (2) is adjusted to 9-11, the ammonia concentration is 5-10 g / L, the temperature is 50-80°C and the solid content is 5-100 g / L, and the rotation speed is adjusted to 350 rpm-200 rpm.
[0070] In the method for preparing the secondary inner layer of the present invention, the pH of the reaction slurry obtained in step (2) is adjusted to 9 to 11, for example, it can be 9, 9.2, 9.4, 9.6, 9.8, 10, 10.2, 10.4, 10.6, 10.8 or 11, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0071] In the method for preparing the secondary inner layer of the present invention, the ammonia concentration of the reaction slurry obtained in step (2) is adjusted to 5 to 10 g / L, for example, it can be 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L or 10 g / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0072] In the method for preparing the secondary inner layer of the present invention, the temperature of the reaction slurry obtained in step (2) is adjusted to 50-80°C, for example, it can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0073] In the method for preparing the secondary inner layer of the present invention, the solid content of the reaction slurry obtained in step (2) is adjusted to 5 to 100 g / L, for example, it can be 5 g / L, 10 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L, 35 g / L, 40 g / L, 45 g / L, 50 g / L, 55 g / L, 60 g / L, 65 g / L, 70 g / L, 75 g / L, 80 g / L, 85 g / L, 90 g / L, 95 g / L or 100 g / L, but is not limited to the listed values, and other values not listed within the numerical range are equally applicable.
[0074] In the method for preparing the secondary inner layer of the present invention, the rotation speed is adjusted to 350-200 rpm, for example, it can be 350 rpm, 320 rpm, 300 rpm, 280 rpm, 260 rpm, 240 rpm, 220 rpm or 200 rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0075] , but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0076] Preferably, in the method for preparing the secondary inner layer, sodium hydroxide solution and aqueous ammonia are used to adjust the pH and ammonia concentration of the reaction solution obtained in step (1).
[0077] Preferably, in the method for preparing the secondary inner layer, the intermediate target particle size is a D50 particle size of 0.6 to 4.5 μm, for example, it can be 0.6 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm or 4.5 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0078] Preferably, in the method for preparing the secondary inner layer, the protective atmosphere comprises nitrogen and / or an inert gas.
[0079] Preferably, in the method for preparing the secondary inner layer, the solid-liquid separation further comprises washing and drying the obtained solid in sequence.
[0080] Preferably, in step (3), the pH of the reaction solution obtained in the previous step is adjusted to 8-11, the ammonia concentration is adjusted to 3-6 g / L, the temperature is adjusted to 50-80°C, the solid content is adjusted to 40-80 g / L, and the rotation speed is adjusted to 200-50 rpm.
[0081] In step (3) of the present invention, the pH of the reaction solution obtained in the previous step is adjusted to 8 to 11, for example, 8, 8.5, 9, 9.5, 10, 10.5 or 11, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0082] In step (3) of the present invention, the ammonia concentration of the reaction solution obtained in the previous step is adjusted to 3 to 6 g / L, for example, 3 g / L, 3.5 g / L, 4 g / L, 4.5 g / L, 5 g / L, 5.5 g / L or 6 g / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0083] In step (3) of the present invention, the temperature of the reaction solution obtained in the previous step is adjusted to 50-80°C, for example, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0084] In step (3) of the present invention, the solid content of the reaction solution obtained in the previous step is adjusted to 40-80 g / L, for example, it can be 40 g / L, 45 g / L, 50 g / L, 55 g / L, 60 g / L, 65 g / L, 70 g / L, 75 g / L or 80 g / L, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0085] In step (3) of the present invention, the rotation speed is adjusted to 200-50 rpm, for example, it can be 200 rpm, 180 rpm, 160 rpm, 140 rpm, 120 rpm, 100 rpm, 80 rpm, 60 rpm or 50 rpm, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0086] Preferably, in step (3), sodium hydroxide solution and aqueous ammonia are used to adjust the pH and ammonia concentration of the reaction solution obtained in the previous step.
[0087] Preferably, the coprecipitation reaction in step (3) is accompanied by stirring at a stirring speed of 200 to 50 rpm, for example, 200 rpm, 170 rpm, 140 rpm, 110 rpm, 80 rpm or 50 rpm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0088] Preferably, the protective atmosphere in step (3) comprises nitrogen and / or an inert gas.
[0089] Preferably, the solid-liquid separation in step (3) further comprises washing and drying the obtained solid in sequence.
[0090] Preferably, in step (4), the pH of the reaction solution obtained in step (3) is adjusted to 10-11, the ammonia concentration is adjusted to 5-10 g / L, the temperature is adjusted to 50-60° C., and the solid content is adjusted to 40-80 g / L.
[0091] In step (4) of the present invention, the pH of the reaction solution obtained in step (3) is adjusted to 10-11, for example, 10, 10.1, 10.2, 10.3, 10.4, 10.5, 10.6, 10.7, 10.8, 10.9 or 11, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0092] In step (4) of the present invention, the ammonia concentration of the reaction solution obtained in step (3) is adjusted to 5 to 10 g / L, for example, 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L or 10 g / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0093] In step (4) of the present invention, the temperature of the reaction solution obtained in step (3) is adjusted to 50-60°C, for example, 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C or 60°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0094] In step (4) of the present invention, the solid content of the reaction solution obtained in step (3) is adjusted to 40 to 80 g / L, for example, it can be 40 g / L, 45 g / L, 50 g / L, 55 g / L, 60 g / L, 65 g / L, 70 g / L, 75 g / L or 80 g / L, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0095] In step (4) of the present invention, the rotation speed is adjusted to 350-500 rpm, for example, it can be 350 rpm, 370 rpm, 390 rpm, 400 rpm, 420 rpm, 440 rpm, 460 rpm, 480 rpm or 500 rpm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0096] Preferably, in step (4), sodium hydroxide solution and aqueous ammonia are used to adjust the pH and ammonia concentration of the reaction solution obtained in step (3).
[0097] Preferably, the protective atmosphere in step (4) comprises nitrogen and / or an inert gas.
[0098] Preferably, the solid-liquid separation in step (4) further includes washing and drying the obtained solid in sequence.
[0099] Preferably, the M salt in the M salt solution in step (5) includes a soluble salt of any one or a combination of at least two of Al, Nb, B, W or Zr, for example, a soluble salt of Al and Nb, a soluble salt of B and W, a soluble salt of W and Zr, or a soluble salt of Al, Nb and B.
[0100] Preferably, the solvent in the M salt solution in step (5) comprises water.
[0101] Preferably, the concentration of the M salt solution in step (5) is 0.01 to 2 mol / L, for example, 0.01 mol / L, 0.02 mol / L, 0.05 mol / L, 0.08 mol / L, 0.1 mol / L, 0.5 mol / L, 0.8 mol / L, 1 mol / L, 1.5 mol / L, 1.8 mol / L or 2 mol / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0102] Preferably, the protective atmosphere in step (5) comprises nitrogen and / or an inert gas.
[0103] As a preferred technical solution of the preparation method of the present invention, the preparation method comprises:
[0104] (I) adding a ternary metal solution, an alkali solution and a complexing agent solution to a reaction bottom solution in parallel, adjusting the pH of the reaction process to 10-12, the ammonia concentration to 5-8 g / L, the temperature to 40-70° C. and the rotation speed to 350-500 rpm, and performing a first stage of co-precipitation. When the D50 particle size of the precipitate reaches 0.5-2 μm, the reaction is stopped, and a first solid-liquid separation is performed to obtain seed crystals and the remaining reaction bottom solution;
[0105] The pH of the reaction base solution is 7.5-12, the ammonia concentration is 0.1-10 g / L, the temperature is 40-70° C., and the dissolved oxygen content is 1-3000 ppm; the molar concentration of the metal ions in the ternary metal solution is 0.1-5 mol / L;
[0106] (II) mixing the obtained seed crystals with water and adding the mixture into the remaining reaction base solution obtained in step (1) to obtain a slurry, and then adding the ternary metal solution, alkali solution and complexing agent solution to the obtained slurry in parallel to obtain a reaction slurry;
[0107] (III) adjusting the pH of the reaction slurry obtained in step (II) to 9-11, the ammonia concentration to 5-10 g / L, the temperature to 50-80° C., and the solid content to 5-100 g / L, and simultaneously adjusting the rotation speed to 350-200 rpm, and performing a coprecipitation reaction in a protective atmosphere to obtain a reaction slurry containing a precipitate with a D50 particle size of 0.6-4.5 μm;
[0108] (IV) adjusting the pH of the reaction slurry obtained in step (III) to 8-11, the ammonia concentration to 3-6 g / L, the temperature to 50-80° C., and the solid content to 40-80 g / L, and simultaneously adjusting the rotation speed to 200-50 rpm, and performing a coprecipitation reaction in a protective atmosphere to obtain a reaction solution containing the first target precipitate, and then stopping the reaction;
[0109] (V) adjusting the pH of the reaction solution obtained in step (IV) to 10-11, the ammonia concentration to 5-10 g / L, the temperature to 50-60° C., and the solid content to 40-80 g / L, and simultaneously adjusting the rotation speed to 350-500 rpm, performing a coprecipitation reaction in a protective atmosphere, and stopping the reaction after obtaining a reaction solution containing the second target precipitate;
[0110] (VI) if only one layer of the stacked structure is prepared, then directly start preparing the M element doped coating shell; if more than one layer of the stacked structure is prepared, then repeat step (IV) and step (V) at least once, and then prepare the M element doped coating shell to obtain a multilayer structure precursor;
[0111] The method for preparing the M element doped coating shell is as follows: keeping the pH, ammonia concentration, temperature and solid content of the reaction solution obtained in the last step (V) unchanged, keeping the rotation speed unchanged, adding the M salt solution, ternary metal solution, alkali solution and complexing agent solution with a concentration of 0.01 to 5 mol / L into the reaction solution obtained in the last step (V) in parallel, carrying out a coprecipitation reaction in a protective atmosphere, stopping the reaction after reaching a D50 particle size of 8 to 20 μm, and obtaining the M element doped coating shell.
[0112] In a third aspect, the present invention provides a solid-state battery positive electrode material, which is prepared from the multilayer structure precursor described in the first aspect.
[0113] In a fourth aspect, the present invention provides a process for preparing the solid-state battery positive electrode material according to the third aspect, the preparation process comprising:
[0114] The multilayer structure precursor is mixed with a lithium source, and then pre-fired at 300-500° C. for 3-5 hours in a pure oxygen atmosphere, ground and then calcined at 500-800° C. for 10-20 hours in a pure oxygen atmosphere to obtain the solid-state battery positive electrode material.
[0115] The preparation process described in the present invention is pre-sintering at 300-500°C in a pure oxygen atmosphere, for example, it can be 300°C, 320°C, 340°C, 360°C, 380°C, 400°C, 420°C, 440°C, 460°C, 480°C or 500°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0116] The preparation process described in the present invention is pre-sintered in a pure oxygen atmosphere for 3 to 5 hours, for example, 3 hours, 3.2 hours, 3.4 hours, 3.6 hours, 3.8 hours, 4 hours, 4.2 hours, 4.4 hours, 4.6 hours, 4.8 hours or 5 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0117] The preparation process described in the present invention is to calcine at 500-800°C in a pure oxygen atmosphere, for example, it can be 500°C, 720°C, 740°C, 760°C, 780°C or 800°C, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0118] The preparation process described in the present invention is calcined in a pure oxygen atmosphere for 10 to 20 hours, for example, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours or 20 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0119] In a fifth aspect, the present invention provides a solid-state battery, comprising the solid-state battery positive electrode material described in the third aspect.
[0120] Compared with the prior art, the present invention has the following beneficial effects:
[0121] (1) The multilayer structure precursor of the solid-state battery positive electrode material provided by the present invention is designed with a multilayer structure, and the loose layers and the dense layers are arranged alternately in the multilayer structure design. On the one hand, it can effectively release the accumulated stress generated during the de-lithiation or lithium insertion process of the positive electrode material, reduce the volume deformation of the positive electrode material particles, thereby improving the structural stability of the material and the cycle performance of the solid-state battery; on the other hand, the multilayer structure can improve the lithium ion embedding and extraction channels, thereby improving the electrochemical performance of the solid-state battery; in addition, the outermost layer of the multilayer structure is designed to be an M element doped coating shell. The introduction of the M element doped coating shell can improve the conductivity of the interface layer, inhibit the side reaction between the positive electrode material and the solid electrolyte interface, and thus make the positive electrode material and the solid-state battery have good electrochemical performance;
[0122] (2) In the preparation method of the multilayer structure precursor provided by the present invention, the porosity of different layers of the multilayer structure precursor is controlled by controlling the pH, ammonia concentration and temperature during the reaction process, thereby obtaining a multilayer structure precursor in which loose layers and dense layers are arranged alternately. BRIEF DESCRIPTION OF THE DRAWINGS
[0123] Figure 1 Schematic diagram of the structure of the multilayer structure precursor of the solid-state battery positive electrode material in Examples 1 to 3.
[0124] Figure 2 This is a SEM image of the multilayer structure precursor of the solid-state battery positive electrode material in Example 1
[0125] Among them, 1-seed crystal; 2-second inner layer; 3-first coating layer; 4-second coating layer; 5-M element doped coating outer shell. DETAILED DESCRIPTION
[0126] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0127] Example 1
[0128] This embodiment provides a Figure 1 The multilayer structure precursor of the solid-state battery positive electrode material shown in the figure comprises a seed crystal with a porosity of 25%, a secondary inner layer with a porosity of 15%, an intermediate coating layer and an M element doped coating shell with a porosity of 15%, wherein the M element is W;
[0129] The intermediate coating layer includes a stacked structure, which includes a first coating layer and a second coating layer with different porosities that are stacked; the porosity of the first coating layer in the stacked structure is greater than the porosity of the second coating layer; the porosity of the first coating layer in the stacked structure is 18%; and the porosity of the second coating layer in the stacked structure is 10%.
[0130] The D50 particle size of the seed crystal is 2 μm; the thickness of the sub-inner layer is 1.3 μm; the thickness of the first coating layer in the stacked structure is independently 2 μm; the thickness of the second coating layer in the stacked structure is independently 2 μm; and the thickness of the M element doped coating shell is 0.7 μm.
[0131] The general chemical formula of the multilayer structure precursor is Ni a Co b Mn c W d (OH)2, where a=0.95, b=0.02, c=0.02, d=0.01, a+b+c+d=1;
[0132] The D50 particle size of the multilayer structure precursor is 8 μm, and the tap density TD is 1.8 g / cm 3 , with a specific surface area of 12 g / cm 3 , the ratio of the (101) peak diffraction intensity to the (001) peak diffraction intensity is 1.0, and the half-peak width of the (101) peak is 0.32.
[0133] The preparation method of the multilayer structure precursor comprises:
[0134] (I) adding a ternary metal solution (a molar ratio of nickel ion, cobalt ion and manganese ion of 0.95:0.02:0.02), a sodium hydroxide solution and an ammonia solution to a reaction bottom solution in parallel, adjusting the pH of the reaction process to 11, the ammonia concentration to 6.5 g / L, the temperature to 55° C. and the rotation speed to 420 rpm, and performing a first stage of co-precipitation. When the D50 particle size of the precipitate reaches 2 μm, the reaction is stopped, and a first solid-liquid separation is performed to obtain a seed crystal and a remaining reaction bottom solution;
[0135] The pH of the reaction solution is 10, the ammonia concentration is 5 g / L, the temperature is 55° C., and the dissolved oxygen content is 1500 ppm; the molar concentration of the metal ions in the ternary metal solution is 2.5 mol / L;
[0136] (II) mixing the obtained seed crystals with water and adding the mixture to the remaining reaction bottom solution obtained in step (1) to obtain a slurry, and then adding the ternary metal solution, sodium hydroxide solution and ammonia water to the obtained slurry in parallel to obtain a reaction slurry;
[0137] (III) adjusting the pH of the reaction slurry obtained in step (II) to 9.5, the ammonia concentration to 7.5 g / L, the temperature to 65° C. and the solid content to 50 g / L, and simultaneously adjusting the rotation speed to 280 rpm, and performing a coprecipitation reaction in a protective atmosphere to obtain a reaction slurry containing a precipitate with a D50 particle size of 3.3 μm;
[0138] (IV) adjusting the pH of the reaction slurry obtained in step (III) to 9.5, the ammonia concentration to 4.5 g / L, the temperature to 65° C. and the solid content to 60 g / L, and simultaneously adjusting the rotation speed to 120 rpm, and performing a coprecipitation reaction in a protective atmosphere to obtain a reaction solution containing the first target precipitate, and then stopping the reaction;
[0139] (V) adjusting the pH of the reaction solution obtained in step (IV) to 10.5, the ammonia concentration to 7.5 g / L, the temperature to 55° C. and the solid content to 60 g / L, and simultaneously adjusting the rotation speed to 420 rpm, and performing a coprecipitation reaction in a protective atmosphere to obtain a reaction solution containing the second target precipitate, and then stopping the reaction;
[0140] (VI) preparing an M element doped coating shell, wherein the method for preparing the M element doped coating shell is as follows: keeping the pH, ammonia concentration, temperature and solid content of the reaction solution obtained in the last step (V) unchanged, keeping the rotation speed unchanged, adding a 2.5 mol / L W salt solution, a ternary metal solution, a sodium hydroxide solution and ammonia water in parallel to the reaction solution obtained in the last step (V), performing a coprecipitation reaction in a protective atmosphere, and stopping the reaction after reaching a D50 particle size of 8 μm, thereby obtaining an M element doped coating shell;
[0141] The obtained multilayer structure precursor was tested by scanning electron microscopy, and the SEM image of the multilayer structure precursor was obtained as shown in FIG. Figure 2 shown.
[0142] Example 2
[0143] This embodiment provides a multilayer structure precursor of a solid-state battery positive electrode material, wherein the multilayer structure precursor comprises a seed crystal with a porosity of 10%, a secondary inner layer with a porosity of 25%, an intermediate coating layer, and an M element doped coating shell with a porosity of 20%, wherein the M element is Zr;
[0144] The intermediate coating layer comprises a first stacking structure and a second stacking structure which are stacked, wherein the first stacking structure and the second stacking structure comprise a first coating layer and a second coating layer which are stacked and have different porosities; the porosity of the first coating layer in the first stacking structure and the second stacking structure is greater than the porosity of the second coating layer; the porosity of the first coating layer in the first stacking structure and the second stacking structure is 10% and the porosity of the second coating layer is 1%;
[0145] The D50 particle size of the seed crystal is 2 μm; the thickness of the sub-inner layer is 2.5 μm; the thickness of the first coating layer in the first stacking structure and the second stacking structure is 2 μm, and the thickness of the second coating layer is 2 μm; the thickness of the M element doped coating shell is 0.01 μm.
[0146] The general chemical formula of the multilayer structure precursor is Ni a Co b Mn c Zr d (OH)2, where a=0.94, b=0.03, c=0.02, d=0.01, a+b+c+d=1;
[0147] The D50 particle size of the multilayer structure precursor is 12.51 μm, and the tap density TD is 1.4 g / cm 3 , with a specific surface area of 20 g / cm 3 The ratio of the (101) peak diffraction intensity to the (001) peak diffraction intensity is 1.3, and the half-peak width of the (101) peak is 0.25.
[0148] The preparation method of the multilayer structure precursor comprises:
[0149] (I) adding a ternary metal solution (a molar ratio of nickel ion, cobalt ion and manganese ion of 0.94:0.03:0.02), a sodium hydroxide solution and an ammonia solution to a reaction bottom solution in parallel, adjusting the pH of the reaction process to 12, the ammonia concentration to 8 g / L, the temperature to 40° C. and the rotation speed to 500 rpm, and performing a first stage of co-precipitation. When the D50 particle size of the precipitate reaches 2 μm, the reaction is stopped, and a first solid-liquid separation is performed to obtain a seed crystal and a remaining reaction bottom solution;
[0150] The pH of the reaction solution is 12, the ammonia concentration is 10 g / L, the temperature is 40° C., and the dissolved oxygen content is 1 ppm; the molar concentration of the metal ions in the ternary metal solution is 0.1 mol / L;
[0151] (II) mixing the obtained seed crystals with water and adding the mixture to the remaining reaction bottom solution obtained in step (1) to obtain a slurry, and then adding the ternary metal solution, sodium hydroxide solution and ammonia water to the obtained slurry in parallel to obtain a reaction slurry;
[0152] (III) adjusting the pH of the reaction slurry obtained in step (II) to 9, the ammonia concentration to 5 g / L, the temperature to 80° C. and the solid content to 100 g / L, and simultaneously adjusting the rotation speed to 350 rpm, and performing a coprecipitation reaction in a protective atmosphere to obtain a reaction slurry containing a precipitate with a D50 particle size of 4.5 μm;
[0153] (IV) adjusting the pH of the reaction slurry obtained in step (III) to 8, the ammonia concentration to 3 g / L, the temperature to 80° C. and the solid content to 80 g / L, and simultaneously adjusting the rotation speed to 200 rpm, and performing a coprecipitation reaction in a protective atmosphere to obtain a reaction solution containing the first target precipitate, and then stopping the reaction;
[0154] (V) adjusting the pH of the reaction solution obtained in step (IV) to 10, the ammonia concentration to 5 g / L, the temperature to 60° C. and the solid content to 80 g / L, and simultaneously adjusting the rotation speed to 500 rpm, and performing a coprecipitation reaction in a protective atmosphere to obtain a reaction solution containing the second target precipitate, and then stopping the reaction;
[0155] (VI) repeating step (IV) and step (V) once, and then preparing an M element doped coating shell to obtain a multilayer structure precursor;
[0156] The method for preparing the M element doped coating shell is as follows: keeping the pH, ammonia concentration, temperature and solid content of the reaction solution obtained in the last step (V) unchanged, keeping the rotation speed unchanged, adding a 5 mol / L Zr salt solution, a ternary metal solution, a sodium hydroxide solution and ammonia water in parallel to the reaction solution obtained in the last step (V), carrying out a coprecipitation reaction in a protective atmosphere, and stopping the reaction after reaching a D50 particle size of 12.51 μm to obtain the M element doped coating shell.
[0157] Example 3
[0158] This embodiment provides a multilayer structure precursor of a solid-state battery positive electrode material, wherein the multilayer structure precursor comprises a seed crystal with a porosity of 45%, a secondary inner layer with a porosity of 5%, an intermediate coating layer and an M element doped coating shell with a porosity of 10%, wherein the M element is Nb;
[0159] The intermediate coating layer comprises a first stacking structure, a second stacking structure and a third stacking structure, wherein the first stacking structure, the second stacking structure and the third stacking structure comprise a first coating layer and a second coating layer having different porosities, wherein the porosity of the first coating layer in the first stacking structure, the second stacking structure and the third stacking structure is greater than the porosity of the second coating layer, and the porosity of the first coating layer in the first stacking structure, the second stacking structure and the third stacking structure is 25% and the porosity of the second coating layer is 20%;
[0160] The D50 particle size of the seed crystal is 0.5 μm; the thickness of the sub-inner layer is 0.1 μm; the thickness of the first coating layer in the first stacking structure, the second stacking structure and the third stacking structure is independently 1.2 μm, and the thickness of the second coating layer is 1 μm; the thickness of the M element doped coating shell is 1 μm.
[0161] The general chemical formula of the multilayer structure precursor is Ni a Co b Mn c Nb d (OH)2; wherein a=0.94, b=0.03, c=0.02, d=0.01, a+b+c+d=1;
[0162] The D50 particle size of the multilayer structure precursor is 8.2 μm, and the tap density TD is 2.2 g / cm 3 , with a specific surface area of 4 g / cm 3 , the ratio of the (101) peak diffraction intensity to the (001) peak diffraction intensity is 0.8, and the half-peak width of the (101) peak is 0.4.
[0163] The preparation method of the multilayer structure precursor comprises:
[0164] (I) adding a ternary metal solution (a molar ratio of nickel ion, cobalt ion and manganese ion of 0.94:0.03:0.02), a sodium hydroxide solution and an ammonia solution to a reaction bottom solution in parallel, adjusting the pH of the reaction process to 10, the ammonia concentration to 5 g / L, the temperature to 70° C. and the rotation speed to 350 rpm, and performing a first stage of co-precipitation. When the D50 particle size of the precipitate reaches 0.5 μm, the reaction is stopped, and a first solid-liquid separation is performed to obtain a seed crystal and a remaining reaction bottom solution;
[0165] The pH of the reaction base solution is 7.5, the ammonia concentration is 0.1 g / L, the temperature is 70° C. and the dissolved oxygen content is 3000 ppm; the molar concentration of the metal ions in the ternary metal solution is 5 mol / L;
[0166] (II) mixing the obtained seed crystals with water and adding the mixture to the remaining reaction bottom solution obtained in step (1) to obtain a slurry, and then adding the ternary metal solution, sodium hydroxide solution and ammonia water to the obtained slurry in parallel to obtain a reaction slurry;
[0167] (III) adjusting the pH of the reaction slurry obtained in step (II) to 11, the ammonia concentration to 10 g / L, the temperature to 50° C. and the solid content to 5 g / L, and simultaneously adjusting the rotation speed to 200 rpm, and performing a coprecipitation reaction in a protective atmosphere to obtain a reaction slurry containing a precipitate with a D50 particle size of 0.6 μm;
[0168] (IV) adjusting the pH of the reaction slurry obtained in step (III) to 11, the ammonia concentration to 6 g / L, the temperature to 50° C. and the solid content to 40 g / L, and simultaneously adjusting the rotation speed to 50 rpm, and performing a coprecipitation reaction in a protective atmosphere to obtain a reaction solution containing the first target precipitate, and then stopping the reaction;
[0169] (V) adjusting the pH of the reaction solution obtained in step (IV) to 11, the ammonia concentration to 10 g / L, the temperature to 50° C. and the solid content to 40 g / L, and simultaneously adjusting the rotation speed to 350 rpm, and performing a coprecipitation reaction in a protective atmosphere to obtain a reaction solution containing the second target precipitate, and then stopping the reaction;
[0170] (VI) Repeating steps (IV) and (V) twice, and then preparing an M element doped coating shell to obtain a multilayer structure precursor;
[0171] The method for preparing the M element doped coating shell is as follows: keeping the pH, ammonia concentration, temperature and solid content of the reaction solution obtained in the last step (V) unchanged, keeping the rotation speed unchanged, adding a Nb salt solution, a ternary metal solution, a sodium hydroxide solution and ammonia water with a concentration of 0.01 mol / L into the reaction solution obtained in the last step (V) in parallel, carrying out a coprecipitation reaction in a protective atmosphere, and stopping the reaction after reaching a D50 particle size of 8.2 μm to obtain the M element doped coating shell.
[0172] Example 4
[0173] This embodiment provides a multilayer structure precursor of a solid-state battery positive electrode material, which is the same as that of Embodiment 1 except that the porosity of the seed crystal in the multilayer structure precursor is 5%.
[0174] Example 5
[0175] This embodiment provides a multilayer structure precursor of a solid-state battery positive electrode material, which is the same as that of Embodiment 1 except that the porosity of the seed crystal in the multilayer structure precursor is 50%.
[0176] Example 6
[0177] This embodiment provides a multilayer structure precursor of a solid-state battery positive electrode material, which is the same as Example 1 except that the sub-inner layer in the multilayer structure precursor is omitted, that is, step (II) of the preparation method of the multilayer structure precursor is omitted.
[0178] Example 7
[0179] This embodiment provides a multilayer structure precursor of a solid-state battery positive electrode material, which is the same as that of Embodiment 1 except that the porosity of the sub-inner layer in the multilayer structure precursor is 3%.
[0180] Example 8
[0181] This embodiment provides a multilayer structure precursor of a solid-state battery positive electrode material, which is the same as that of Embodiment 1 except that the porosity of the sub-inner layer in the multilayer structure precursor is 30%.
[0182] Example 9
[0183] This embodiment provides a multilayer structure precursor of a solid-state battery positive electrode material, which is the same as that of Embodiment 1 except that the porosity of the M element doped coating shell in the multilayer structure precursor is 5%.
[0184] Example 10
[0185] This embodiment provides a multilayer structure precursor of a solid-state battery positive electrode material, which is the same as that of Embodiment 1 except that the porosity of the M element doped coating shell in the multilayer structure precursor is 25%.
[0186] Embodiment 11
[0187] This embodiment provides a multilayer structure precursor of a solid-state battery positive electrode material, which is the same as Embodiment 1 except that the thickness of the M element doped coating shell in the multilayer structure precursor is 0.005 μm.
[0188] Example 12
[0189] This embodiment provides a multilayer structure precursor of a solid-state battery positive electrode material, which is the same as Embodiment 1 except that the thickness of the M element doped coating shell in the multilayer structure precursor is 2 μm.
[0190] Comparative Example 1
[0191] This comparative example provides a multilayer structure precursor of a solid-state battery positive electrode material, which is the same as Example 1 except that the first coating layer in the stacked structure in the intermediate coating layer is omitted.
[0192] Comparative Example 2
[0193] This comparative example provides a multilayer structure precursor of a solid-state battery positive electrode material, which is the same as Example 1 except that the second coating layer in the stacked structure in the intermediate coating layer is omitted.
[0194] Comparative Example 3
[0195] This comparative example provides a multilayer structure precursor of a solid-state battery positive electrode material, which is the same as Example 1 except that the middle coating layer of the multilayer structure precursor is omitted.
[0196] Comparative Example 4
[0197] This comparative example provides a multilayer structure precursor of a solid-state battery positive electrode material, which is the same as Example 1 except that the M element doping coating shell of the multilayer structure precursor is omitted.
[0198] The multilayer structure precursor provided in the above embodiments and comparative examples is used to prepare solid-state battery positive electrode materials. The method for preparing solid-state battery positive electrode materials is as follows: the precursor and lithium carbonate are evenly mixed according to a molar ratio of lithium in lithium carbonate to metal ions in the precursor of 1:1.05, and the mixture is placed in a tubular furnace for sintering. The sintering atmosphere is pure oxygen, and the mixture is pre-fired at 400°C for 4 hours. After the pre-fired is completed, the mixture is naturally cooled to room temperature. The sample is taken out, simply ground and then sintered at high temperature. The mixture is then calcined at 800°C for 15 hours. After the calcination is completed, the mixture is naturally cooled to room temperature. The solid-state battery positive electrode material can be obtained by grinding and sieving the sample.
[0199] The prepared solid-state battery positive electrode material is used to prepare a lithium-ion battery: the obtained coated modified ternary positive electrode material, conductive carbon black SP (TIMCAL) and polyvinylidene fluoride PVDF (HSV900) are mixed in a mass ratio of 90:5:5, N-methylpyrrolidone is used as a solvent, and the mixture is stirred into a slurry. The obtained slurry is evenly coated on an aluminum foil with a scraper with a coating gap of 100 um; after coating, it is first blown dry, then rolled and cut into circular electrode sheets, and then vacuum dried at 120° C. and the weight of the electrode sheets is weighed to obtain a button half-battery positive electrode sheet; a metal lithium sheet is selected as the negative electrode, a PP microporous membrane is selected as the diaphragm, and a lithium battery basic electrolyte is selected as the electrolyte. The positive electrode sheet, the metal lithium sheet, the diaphragm and the electrolyte are assembled to obtain a button battery;
[0200] The charge and discharge test was carried out at a voltage window of 2.8-4.3V with 0.1C / 0.1C charge and discharge, and the 0.1C rate performance and the capacity retention rate after 100 cycles were obtained as shown in Table 1.
[0201] Table 1
[0202] Capacity retention rate (%) 0.1C rate (mAh / g) Example 1 92 214 Example 2 91 199 Example 3 94 207 Example 4 81 164 Example 5 79 158 Example 6 79 147 Example 7 80 156 Example 8 78 158 Example 9 76 154 Example 10 75 161 Embodiment 11 78 167 Example 12 82 163 Comparative Example 1 81 162 Comparative Example 2 83 164 Comparative Example 3 79 158 Comparative Example 4 82 168
[0203] From Table 1, we can get:
[0204] (1) The solid-state battery prepared by the multilayer structure precursor provided in Examples 1 to 3 of the present invention exhibits excellent cycle stability and high rate performance;
[0205] (2) By comparing Example 1 with Examples 4 and 5, it can be seen that the porosity of the core in the multilayer structure precursor of the present invention affects the performance of the solid-state battery; when the porosity of the core is too small or too large, the capacity retention rate of the solid-state battery will decrease and the rate performance will deteriorate. This is because the porosity is too small or too large, which is not conducive to the release or embedding of lithium ions, thereby reducing the battery performance;
[0206] (3) By comparing Example 1 with Example 6, it can be seen that the sub-inner layer in the multilayer structure precursor of the present invention affects the performance of the solid-state battery; when the sub-inner layer is omitted, the capacity retention rate of the solid-state battery becomes smaller and the rate performance becomes worse. This is because the dense layer and the loose layer do not appear alternately, and the accumulated stress cannot be released in time;
[0207] (4) By comparing Example 1 with Examples 7 and 8, it can be seen that the porosity of the sub-inner layer in the multilayer structure precursor of the present invention affects the performance of the solid-state battery; when the porosity of the sub-inner layer is too small or too large, the capacity retention rate of the solid-state battery will decrease and the rate performance will deteriorate. This is because these two situations cannot regulate the lithium ion escape or embedding channel, which deteriorates the battery performance;
[0208] (5) By comparing Example 1 with Examples 9 and 10, it can be seen that the porosity of the M-doped coating shell in the multilayer structure precursor of the present invention will affect the performance of the solid-state battery; when the porosity of the M-doped coating shell is relatively small, the capacity retention rate of the solid-state battery will be reduced and the rate performance will be poor. This is because the small porosity is not conducive to the escape and embedding of lithium ions; when the porosity of the M-doped coating shell is relatively large, the capacity retention rate of the solid-state battery will be reduced and the rate performance will be poor. This is because the large porosity makes it easy for the electrode to undergo side reactions, which deteriorates the battery performance.
[0209] (6) By comparing Example 1 with Examples 11 and 12, it can be seen that the thickness of the M element doped coating shell in the multilayer structure precursor of the present invention will affect the performance of the solid-state battery; when the thickness of the M element doped coating shell is too small, the capacity retention rate of the solid-state battery will decrease and the rate performance will deteriorate. This is because the thickness of the doped coating shell is too small and the side reactions cannot be effectively suppressed; when the thickness of the M element doped coating shell is too large, the capacity retention rate of the solid-state battery will decrease and the rate performance will deteriorate. This is because the doped coating shell is too large, which blocks the diffusion channel of lithium ions;
[0210] (7) By comparing Example 1 with Comparative Examples 1 to 4, it can be seen that the multilayer structure precursor of the solid-state battery positive electrode material provided by the present invention is designed with a multilayer structure, and the loose layer and the dense layer are arranged alternately in the multilayer structure design. On the one hand, it can effectively release the accumulated stress generated during the delithiation or insertion of the positive electrode material, reduce the volume deformation of the positive electrode material particles, thereby improving the structural stability of the material and the cycle performance of the solid-state battery; on the other hand, the multilayer structure can improve the lithium ion embedding and extraction channels, thereby improving the electrochemical performance of the solid-state battery; in addition, the outermost layer of the multilayer structure is designed to be an M element doped coating shell. The introduction of the M element doped coating shell can improve the conductivity of the interface layer, inhibit the side reaction between the positive electrode material and the solid electrolyte interface, and thus make the positive electrode material and the solid-state battery have good electrochemical performance.
[0211] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A multilayer structure precursor of a solid-state battery positive electrode material, characterized in that: The multi-layer structure precursor comprises a seed crystal, an intermediate coating layer and an M element doped coating shell; The intermediate coating layer includes at least one stacked structure, and the stacked structure includes a first coating layer and a second coating layer with different porosities that are stacked.
2. The multilayer structure precursor according to claim 1, characterized in that: The multi-layer structure precursor further includes a secondary inner layer disposed between the seed crystal and the intermediate coating layer; Preferably, the porosity of the seed crystal is 10 to 45%; Preferably, the porosity of the sub-inner layer is 5-25%; Preferably, the porosity of the first coating layer in the stacked structure is greater than the porosity of the second coating layer; Preferably, the porosity of the first coating layer in the stacked structure is independently 10 to 25%; Preferably, the porosity of the second coating layer in the stacked structure is independently 1 to 20%; Preferably, the porosity of the M element doped coating shell is 10-20%; Preferably, the D50 particle size of the seed crystal is 0.5 to 2 μm; Preferably, the thickness of the secondary inner layer is 0.1 to 2.5 μm; Preferably, the thickness of the first coating layer in the stacked structure is independently 0.5 to 2 μm; Preferably, the thickness of the second coating layer in the stacked structure is independently 0.5 to 2 μm; Preferably, the M element includes any one or a combination of at least two of Al, Nb, B, W or Zr; Preferably, the thickness of the M element doped coating shell is 0.01-1 μm.
3. The multilayer structure precursor according to claim 1 or 2, characterized in that: The general chemical formula of the multilayer structure precursor is Ni a Co b Mn c M d (OH)2; wherein M is any one of Al, Nb, B, W or Zr or a combination of at least two elements, 0.9 <a<1,0<b≤0.09,0<c≤0.09,0<d<0.05,a+b+c+d=1; Preferably, the D50 particle size of the multilayer structure precursor is 8 to 20 μm; Preferably, the tap density TD of the multilayer structure precursor is 1.4 to 2.2 g / cm 3 ; Preferably, the specific surface area of the multilayer structure precursor is 4 to 20 g / cm 3 ; Preferably, the ratio of the (101) peak diffraction intensity to the (001) peak diffraction intensity of the multilayer structure precursor is 0.8 to 1.3, and the half-peak width of the (101) peak is 0.25 to 0.
4.
4. A method for preparing the multilayer structure precursor according to any one of claims 1 to 3, characterized in that: The preparation method comprises: (1) adding a ternary metal solution, an alkali solution and a complexing agent solution to a reaction bottom solution in parallel, adjusting the pH, ammonia concentration, temperature and rotation speed of the reaction process, and performing a first stage of co-precipitation. When the precipitate reaches an initial target particle size, the reaction is stopped, and a first solid-liquid separation is performed to obtain seed crystals and a remaining reaction bottom solution; (2) mixing the obtained seed crystals with water and adding the mixture into the remaining reaction base solution obtained in step (1) to obtain a slurry, and then adding the ternary metal solution, alkali solution and complexing agent solution to the obtained slurry in parallel to obtain a reaction slurry; (3) adjusting the pH, ammonia concentration, temperature and solid content of the reaction slurry obtained in the previous step, and simultaneously adjusting the rotation speed, performing a coprecipitation reaction in a protective atmosphere, and stopping the reaction after obtaining a reaction solution containing the first target precipitate; (4) adjusting the pH, ammonia concentration, temperature and solid content of the reaction solution obtained in step (3), and simultaneously adjusting the rotation speed, performing a coprecipitation reaction in a protective atmosphere, and stopping the reaction after obtaining a reaction solution containing the second target precipitate; (5) If only one layer of the stacked structure is prepared, then directly start preparing the M element doped coating shell; if more than one layer of the stacked structure is prepared, then repeat step (3) and step (4) at least once, and then prepare the M element doped coating shell to obtain a multilayer structure precursor; The method for preparing the M element doped coating shell is as follows: keeping the pH, ammonia concentration, temperature and solid content of the reaction solution obtained in the last step (4) unchanged, keeping the rotation speed unchanged, adding the M salt solution, the ternary metal solution, the alkali solution and the complexing agent solution to the reaction solution obtained in the last step (4) in parallel, carrying out a coprecipitation reaction in a protective atmosphere, and stopping the reaction after reaching the end target particle size to obtain the M element doped coating shell.
5. The preparation method according to claim 4, characterized in that: The step between step (2) and step (3) also includes the preparation of a secondary inner layer, and the method for preparing the secondary inner layer is: The pH, ammonia concentration, temperature and solid content of the reaction slurry obtained in step (2) are adjusted, and the rotation speed is adjusted simultaneously to carry out a coprecipitation reaction in a protective atmosphere to obtain a reaction slurry containing a precipitate of an intermediate target particle size.
6. The preparation method according to claim 5, wherein the molar concentration of the metal ions in the ternary metal solution in step (1) is 1 to 5 mol / L; Preferably, the pH of the reaction liquid in step (1) is 7.5-12, the ammonia concentration is 0.1-10 g / L, the temperature is 40-70° C., and the dissolved oxygen content is 1-3000 ppm; Preferably, in step (1), the pH of the reaction process is adjusted to 10-12, the ammonia concentration is 5-8 g / L, the temperature is 40-70° C. and the rotation speed is 350-500 rpm; Preferably, the initial target particle size in step (1) is a D50 particle size of 0.5 to 2 μm; Preferably, in the method for preparing the secondary inner layer, the pH of the reaction slurry obtained in step (2) is adjusted to 9-11, the ammonia concentration is 5-10 g / L, the temperature is 50-80° C., the solid content is 5-100 g / L, and the rotation speed is adjusted to 350 rpm-200 rpm; Preferably, in the method for preparing the secondary inner layer, the intermediate target particle size is a D50 particle size of 0.6 to 4.5 μm; Preferably, in step (3), the pH of the reaction solution obtained in the previous step is adjusted to 8-11, the ammonia concentration is adjusted to 3-6 g / L, the temperature is adjusted to 50-80° C., the solid content is adjusted to 40-80 g / L, and the rotation speed is adjusted to 200-50 rpm; Preferably, in step (4), the pH of the reaction solution obtained in step (3) is adjusted to 10-11, the ammonia concentration is 5-10 g / L, the temperature is 50-60° C., the solid content is 40-80 g / L, and the rotation speed is adjusted to 350-500 rpm; Preferably, the concentration of the M salt solution in step (5) is 0.01 to 2 mol / L; Preferably, the final target particle size in step (5) is a D50 particle size of 8 to 20 μm.
7. The preparation method according to any one of claims 4 to 6, characterized in that: The preparation method comprises: (I) adding a ternary metal solution, an alkali solution and a complexing agent solution to a reaction bottom solution in parallel, adjusting the pH of the reaction process to 10-12, the ammonia concentration to 5-8 g / L, the temperature to 40-70° C. and the rotation speed to 350-500 rpm, and performing a first stage of co-precipitation. When the D50 particle size of the precipitate reaches 0.5-2 μm, the reaction is stopped, and a first solid-liquid separation is performed to obtain seed crystals and the remaining reaction bottom solution; The pH of the reaction base solution is 7.5-12, the ammonia concentration is 0.1-10 g / L, the temperature is 40-70° C., and the dissolved oxygen content is 1-3000 ppm; the molar concentration of the metal ions in the ternary metal solution is 0.1-5 mol / L; (II) mixing the obtained seed crystals with water and adding the mixture into the remaining reaction base solution obtained in step (1) to obtain a slurry, and then adding the ternary metal solution, alkali solution and complexing agent solution to the obtained slurry in parallel to obtain a reaction slurry; (III) adjusting the pH of the reaction slurry obtained in step (II) to 9-11, the ammonia concentration to 5-10 g / L, the temperature to 50-80° C., and the solid content to 5-100 g / L, and simultaneously adjusting the rotation speed to 350-200 rpm, and performing a coprecipitation reaction in a protective atmosphere to obtain a reaction slurry containing a precipitate with a D50 particle size of 0.6-4.5 μm; (IV) adjusting the pH of the reaction slurry obtained in step (III) to 8-11, the ammonia concentration to 3-6 g / L, the temperature to 50-80° C., and the solid content to 40-80 g / L, and simultaneously adjusting the rotation speed to 200-50 rpm, and performing a coprecipitation reaction in a protective atmosphere to obtain a reaction solution containing the first target precipitate, and then stopping the reaction; (V) adjusting the pH of the reaction solution obtained in step (IV) to 10-11, the ammonia concentration to 5-10 g / L, the temperature to 50-60° C., and the solid content to 40-80 g / L, and simultaneously adjusting the rotation speed to 350-500 rpm, performing a coprecipitation reaction in a protective atmosphere, and stopping the reaction after obtaining a reaction solution containing the second target precipitate; (VI) if only one layer of the stacked structure is prepared, then directly start preparing the M element doped coating shell; if more than one layer of the stacked structure is prepared, then repeat step (IV) and step (V) at least once, and then prepare the M element doped coating shell to obtain a multilayer structure precursor; The method for preparing the M element doped coating shell is as follows: keeping the pH, ammonia concentration, temperature and solid content of the reaction solution obtained in the last step (V) unchanged, keeping the rotation speed unchanged, adding the M salt solution, ternary metal solution, alkali solution and complexing agent solution with a concentration of 0.01 to 5 mol / L into the reaction solution obtained in the last step (V) in parallel, carrying out a coprecipitation reaction in a protective atmosphere, stopping the reaction after reaching a D50 particle size of 8 to 20 μm, and obtaining the M element doped coating shell.
8. A solid-state battery positive electrode material, characterized in that: The solid-state battery positive electrode material is prepared from the multilayer structure precursor according to any one of claims 1 to 3.
9. A process for preparing the solid-state battery positive electrode material according to claim 8, characterized in that: The preparation process comprises: The multilayer structure precursor is mixed with a lithium source, and then pre-fired at 300-500° C. for 3-5 hours in a pure oxygen atmosphere, ground and then calcined at 500-800° C. for 10-20 hours in a pure oxygen atmosphere to obtain the solid-state battery positive electrode material.
10. A solid-state battery, characterized in that: The solid-state battery comprises the solid-state battery positive electrode material according to claim 8.
Citation Information
Patent Citations
Multi-layer structure precursor for lithium ion battery, positive electrode material and preparation method thereof
CN112607791A
Cited By
Precursor containing primary particles distributed along radial direction and preparation method and application thereof
CN121394347A